Characterization of a re‐engineered, mesothelin‐targeted Pseudomonas exotoxin fusion protein for lung cancer therapy. Issue 8 (14th July 2016) - Bauss, Frieder; Lechmann, Martin; Krippendorff, Ben-Fillippo; Staack, Roland; Herting, Frank; Festag, Matthias; Imhof-Jung, Sabine; Hesse, Friederike; Pompiati, Marc; Kollmorgen, Gwendlyn; da Silva Mateus Seidl, Rita; Bossenmaier, Birgit; et al.
Abstract : Mesothelin overexpression in lung adenocarcinomas correlates with the presence of activating KRAS mutations and poor prognosis. Hence SS1P, a mesothelin‐targeted immunotoxin, could offer valuable treatment options for these patients, but its use in solid tumor therapy is hampered by high immunogenicity and non‐specific toxicity. To overcome both obstacles we developed RG7787, a de‐immunized cytotoxic fusion protein comprising a humanized SS1 Fab fragment and a truncated, B‐cell epitope silenced, 24 kD fragment of Pseudomonas exotoxin A (PE24). Reactivity of RG7787 with sera from immunotoxin‐treated patients was >1000 fold reduced. In vitro RG7787 inhibited cell viability of lung cancer cell lines with picomolar potency. The pharmacokinetic properties of RG7787 in rodents were comparable to SS1P, yet it was tolerated up to 10 fold better without causing severe vascular leak syndrome or hepatotoxicity. A pharmacokinetic/pharmacodynamic model developed based on NCI‐H596 xenograft studies showed that for RG7787 and SS1P, their in vitro and in vivo potencies closely correlate. At optimal doses of 2–3 mg/kg RG7787 is more efficacious than SS1P. Even large, well established tumors (600 mm3) underwent remission during three treatment cycles with RG7787. Also in two patient‐derived lung cancer xenograft models, Lu7336 and Lu7187, RG7787 showed anti‐tumor efficacy. In monotherapy two treatment cycles were moderately efficacious in the Lu7336 model but showed good anti‐tumor activity in the KRAS mutant Lu7187 model (26% and 80% tumor growth inhibition, respectively). Combination of RG7787 with standard chemotherapies further enhanced efficacy in both models achieving near complete eradication of Lu7187 tumors. Highlights: Immunogenicity and off‐target toxicity hamper the therapeutic use of immunotoxins. Re‐engineering the immunotoxin format reduces antigenicity and toxicity. A re‐engineered immunotoxin against mesothelin potently kills lung cancer cells. Combining it with chemotherapy shrinks patient‐derived KRAS mutant lung tumors.